Two Views of the International Monetary System - Barry Eichengreen (Intereconomics, 2019)
Distinguishing between two different schools of thought that are named after two different universities, Harvard and Berkeley, the article looks at the evolution, past and future, of the international monetary system. While the empirical view holds that the system will remain unipolar and dollar-based, the opposing view uses history to contend that it may potenially evolve away from the dollar into a multipolar system.
Keywords: 330